Qualifications Recognition Going Global: An International Convention under UNESCO’s Auspices - Uvalić-Trumbić, Stamenka (International Higher Education, 2020)
In November 2019, UNESCO’s General Conference adopted a Global Convention on the Recognition of Qualifications. The convention is the result of preparatory work by experts, amendments put forward by governments, and consensus reached on the text over the period of eight years. This article presents its origins, the innovations that the convention brings to international mobility and migration, and the next steps in its implementation.